Social Studies in the Era of GenAI - William B. Russell; Stewart Waters; Matthew Hensley (Research in Social Sciences and Technology- OpenED Network, 2026)
As GenAI continues to reshape how we access information, communicate, and understand the world, social studies education must adapt to prepare learners for civic life in an increasingly automated and algorithm-driven society. From AI-generated content and multi-media to predictive policing and algorithmic bias, today’s students face unprecedented ethical, historical, and civic questions that demand thoughtful exploration.